Knowledge and Perceptions on Dementia in Middle-Age Adults for Elderly Preparation: A Case Study in Ban Pho Sa-nga, Tha Pho Subdistrict, Det Udom District, Ubon Ratchathani Province - Promkaew, Orathai; Chantasan, Jittima; Kaewbungrueang , Chuthamat; Somya, Jenjira (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2022)
Dementia in the elderly is one problem that hinders their lifestyle. Understanding the said problem in middle-age adults is preparing people into the elderly for the prevention of dementia. The purpose of this research was to study and assess knowledge and perception of dementia in middle-aged adults. Samples from simple randomization are middle-aged adults between the ages of 40-60 years at Ban Pho Sanga. This study was a questionnaire consisting of general information, the knowledge assessment form about dementia and the perception about and dementia in middle-aged adults. The statistics of data analysis consisted of number and percentage. The results showed two parts. 1) The sample group knew the meaning of dementia, causes of dementia, factors that cause dementia, the effects of dementia and treatment of dementia at a high level, 83.3 %, 73.1 %, 73.9 %, 88.4 % and 67.6 %, respectively. knowledge of the practice to prevent dementia in the moderate level, 58.3% and had received information about dementia 59 % from television, 53.12 %, wanted to gain knowledge of dementia from books/manuals, the highest 38%. 2) The sample group had a high level of perception about dementia, 96.16% of middle-aged adults had a high level of knowledge and perception about dementia. But still have knowledge of how to act to prevent dementia at a low level, Therefore the knowledge of how to prevent dementia should be promoted among middle-aged adults in preparation for the next old age.